Political Participation of People in Ban Pet Sub-district Municipality, Muang District, Khon Kaen Province: Political Participation of People in Ban Pet Sub-district Municipality, Muang District, Khon Kaen Province - Chamnankar, Massaporn; Wankam, Arunprapai; Insorn, Mutita; Prakruakutrarasatratikun; Teskamjorn, Kittipat (RATANABUTH JOURNAL, 2023)
Political involvement can be seen in political participation from the past. Since the election of the mayor Members of the municipal council or conducting political activities in the Ban Pet area usually have very few people participating, or it may be because Ban Pet Sub-district is a semi-urban area where people are interested in doing business. Occupations that require more competition or working in the city As a result, people do not pay attention to political participation as seriously as they should. The purpose of this research was to study the political participation of people in Ban Pet Sub-district Municipality, Muang District, Khon Kaen Province. and to compare by personal factors and political participation of the people in the municipality of Ban Pet Sub-district, Muang District, Khon Kaen Province. This research used quantitative research methodology. The population of this research is people living in Ban Pet Subdistrict Municipality, Muang District, Khon Kaen Province. A random sample of 400 people was analyzed by frequency, percentage, total mean, and statistics used to test the hypothesis: t-Test (Independent samples). Statistically significant at the 0.05 level. sample people Political participation was at a moderate level . The hypothesis test between personal factors and political participation found that Gender and length of residence are different. There was no difference in political participation. Age, income, occupation, education level and marital status were different. resulting in different political participation.